1993
DOI: 10.1136/jmg.30.4.293
|View full text |Cite
|
Sign up to set email alerts
|

Suicide risk in Huntington's disease.

Abstract: In order to evaluate the relevance of suicide risk in families affected by Huntington's disease (HD), 2793 subjects registered with the National Huntington's Disease Research Roster were studied. Suicide was the reported cause of death in 205 subjects (7-3%). This group included affected and possibly affected subjects, subjects at 50% and 25% risk, possibly at risk subjects, and normal relatives. In all categories suicide was more frequent than in the general US population. The data suggest that suicide is qui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
4

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(69 citation statements)
references
References 8 publications
2
58
0
4
Order By: Relevance
“…In addition to motor and cognitive impairments, patients with HD frequently experience psychiatric disturbances, such as anxiety and depression (Di Maio et al, 1993), that severely reduce their daily functioning and quality of life (Hamilton et al, 2003;Wheelock et al, 2003). In the brains of HD mice treated with lithium and VPA together, the activity of GSK-3b and HDACs was consistently decreased, and expression of BDNF and HSP70 was rapidly elevated and sustained .…”
Section: Hdmentioning
confidence: 99%
“…In addition to motor and cognitive impairments, patients with HD frequently experience psychiatric disturbances, such as anxiety and depression (Di Maio et al, 1993), that severely reduce their daily functioning and quality of life (Hamilton et al, 2003;Wheelock et al, 2003). In the brains of HD mice treated with lithium and VPA together, the activity of GSK-3b and HDACs was consistently decreased, and expression of BDNF and HSP70 was rapidly elevated and sustained .…”
Section: Hdmentioning
confidence: 99%
“…6 The suicide rate among patients with Huntington disease varies between 3% and 7.3%. 17 The aim of our study was to evaluate echogenicity of the basal ganglia, especially in the brain stem raphe, and to correlate ultrasound findings with psychiatric features in particu lar, but also with neurologic and cognitive features.…”
Section: Introductionmentioning
confidence: 99%
“…Using the data obtained from the Behavioral Inventory, it was observed that the SG when compared to the CG showed statistically significant differences in internalizing factors (Table 1, Figure 2) and total problems (Table 1; Figure 4), suggesting that the behavioral profile with changes involves not only the individual but also the environment where he is inserted, consequently showing losses in his social relation [11][12][13][14] .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding quality of life, there are reports of suicide justified by depression and physical dependence caused by the impact of symptoms on daily activities 11,12 . Therefore, the DH impairs the mental health of individuals and may be observed suffering and emotional stress among family throughout the course of the disease 13,14 .…”
Section: Discussionmentioning
confidence: 99%